Pengembangan Lembar Kerja Peserta Didik Elektronik (E-LKPD) Berbasis Liveworksheets untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas V SDN Demaan - Nabeella Rachma Tika Ghaisani; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2023)
The lack of use of Student Worksheets (known with LKPD) at SDN Demaan has an impact on student learning outcomes. This research is Research and Development which refers to the Borg and Gall model. This study aims to develop and test the feasibility, practicality, and effectiveness of liveworksheet-based E-LKPD. The population in this study amounted to 30 with 8 small-scale test subjects in VB class students and 22 large-scale test subjects in VA class SD Negeri Demaan. Data collection techniques used test techniques (pretest-posttest) and non-tests in the form of observations, questionnaires, interview results, and document data. The validation results by the material, media, and language expert validators show that the liveworksheet-based E-LKPD has met the valid criteria. Based on the results of the pretest-posttest, it is known that the E-LKPD based on liveworksheets is effective for improving student learning outcomes as indicated by the results of an increase in the average pretest score by 57 to, and 84 during the posttest and the n gain test results obtained <g> gain value of 0 .62 in the medium category. Based on the results of the response questionnaire that was distributed, a very positive response was obtained from teachers and students. From these results, it can be concluded that the E-LKPD based on liveworksheets is effective for improving science learning outcomes and is feasible and practical to use in the learning of class V students at SD Negeri Demaan.